2017
DOI: 10.4155/fmc-2017-0118
|View full text |Cite
|
Sign up to set email alerts
|

New Insights for the Use of Quercetin Analogs in Cancer Treatment

Abstract: The studied compounds represent suitable leads for the development of innovative anticancer drugs. [Formula: see text].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 60 publications
0
48
0
Order By: Relevance
“…BCP, which is more than 25% of the essential oil from Pamburus missionis, has synergistic effect with two other important components of the essential oil, phytol (8) and aromadendrene oxide (9) (Figure 3), resulting in antitumor activity against A431 and HaCaT cell lines, by blocking the cell in phase G0/G1 or sub-G1. The mechanism of action is associated to ROS production [69] and the mitochondrial membrane potential loss, by increasing Bax expression and decreasing Bcl-2 expression. Bax and Bak oligomers form pores, which increase the permeability of the external mitochondrial membrane, releasing cytochrome c in the cytoplasm, which is an apoptosis characterizing event [70][71][72].…”
Section: β-Caryophyllene and Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…BCP, which is more than 25% of the essential oil from Pamburus missionis, has synergistic effect with two other important components of the essential oil, phytol (8) and aromadendrene oxide (9) (Figure 3), resulting in antitumor activity against A431 and HaCaT cell lines, by blocking the cell in phase G0/G1 or sub-G1. The mechanism of action is associated to ROS production [69] and the mitochondrial membrane potential loss, by increasing Bax expression and decreasing Bcl-2 expression. Bax and Bak oligomers form pores, which increase the permeability of the external mitochondrial membrane, releasing cytochrome c in the cytoplasm, which is an apoptosis characterizing event [70][71][72].…”
Section: β-Caryophyllene and Cancermentioning
confidence: 99%
“…In detail, in the latter cell line, the BCP determines a rise of the intracellular concentrations in the drug, probably by increasing the permeability of the cell membrane [13]. The mechanism of action is associated to ROS production [69] and the mitochondrial membrane potential loss, by increasing Bax expression and decreasing Bcl-2 expression. Bax and Bak oligomers form pores, which increase the permeability of the external mitochondrial membrane, releasing cytochrome c in the cytoplasm, which is an apoptosis characterizing event [70][71][72].…”
Section: β-Caryophyllene and Cancermentioning
confidence: 99%
“…Perhaps, the most important property of this flavonoid is its antioxidant effect. In addition, quercetin can be useful in cancer prevention (Iacopetta et al, ) and is known to have antiallergic, anti‐inflammatory, and antiviral activities (Y. Liu et al, ). Most importantly, quercetin impedes the propagation of various types of cancers, such as lung, prostate, liver, breast, colon, and cervical (Y. Liu et al, ); these anticancer properties are exerted through various mechanisms that involve cellular signaling and the ability to inhibit enzymes responsible for the activation of carcinogens.…”
Section: Introductionmentioning
confidence: 99%
“…The primary mechanism of action of these compounds is their anti/pro-oxidant effect [14][15][16]. Some examples of polyphenols with anti cancer effect are flavonoids such as quercetin, kaempferol, fisetin, myricetin (Myr), and phenolic acids such as gallic acid (GA), protocatechuic acid and rosmarinic acid [6,8,10,17]. Recent studies have demonstrated that Myr and GA particularly, could have interesting applications in the treatment of cancer [18,19].…”
Section: Introductionmentioning
confidence: 99%